ANALISA ASPEK UNDANG-UNDANG LALU LINTAS DAN ANGKUTAN JALAN PADA KECELAKAAN TUNGGAL KENDARAAN BERMOTOR - Surbakti, Sangapta; Zarzani, T Riza; Fitrianto, Bambang; Anwar, Yohny; Sinaga, Hary Angga (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
According to data from the Central Bureau of Statistics 2017, traffic accidents in Indonesia have increased the number of cases since 2013. In 2016, the composition of accident victims reached 71.38% who had minor injuries, 13.25% had serious injuries, and 15.37% died. world. Accidents can involve one or more vehicles. An accident involving one vehicle is called a single accident. According to Law No. 22 of 2009 on Traffic and Road Transportation (LAJ Law), a single accident is a traffic accident. Case of a male between fifty and sixty years of age, had a single accident hitting a tree. When the person falls, the helmet comes off. So that the person has abrasions on the forehead, neck, thighs and knees. Bruised on the chest and left hip. Fractures in the anterior skull, maxilla, and upper leg fractures accompanied by brain swelling and bleeding. The classification of injuries according to Article 229 of the LAJ Law states there are only two qualifications of injuries, namely minor injuries and serious injuries. This person has a condition that is classified as severe because the injury to this person causes death.